TANGGUNG GUGAT PERDATA ATAS KERUGIAN KONSUMEN TERHADAP PELAKU USAHA DALAM TRANSAKSI ONLINE SECARA CASH ON DELIVERY (COD) DI E-COMMERCE SHOPEE INDONESIA - Devi Narayan Wijaya; Subekti; Nur Handayati; Marwiyah, Siti (Jurnal Hukum Ius Publicum, 2024)
The results of this study show that the form of liability claimed by the entrepreneur is compensation according to the large loss suffered by consumers, as well as the legal relationship of the parties in the online sale, is a binding contractual relationship for the parties. E-Commerce Shopee, as the organizer of the electronic system and third parties in online sale transactions, is not entirely responsible for the losses arising from negligence by the parties (penjual dan pembeli). Shopee tends to act as a mediator in the mediation process between the seller and buyer in a dispute, with the responsibility to facilitate communication between the parties. The problem in this study also concerns the Perdata Claims on Consumer Loss Against Entrepreneurs in Online Transactions by Cash On Delivery (COD) in E-Commerce Shopee Indonesia. This kind of research is normative law. In many cases, Shopee does not fully fulfil the roles and responsibilities as laid down in government laws and regulations. Therefore, governments, especially the Ministry of Communications and Information Technology as the authority, should emphasize specifically to what extent the role and form of liability of the system operator in the system is responsible in the settlement of disputes between the seller and the buyer. This can be done through the refinement of legislation that regulates more detailed obligations and responsibilities of online market platforms such as Shopee in dealing with Customer Liability Claims for Consumer Loss Against Entrepreneurs in Online Cash On Delivery (COD) Transactions in E-Commerce Shopee Indonesia.